(untitled) (Jalalabad Medical Journal, 2025)
The nutritional status of adolescents impacts on the development of a country, as they are the striking force of a nation. But still now, malnutrition is one of the major public health problems in Bangladesh. This study aimed to see the nutritional status of adolescents at the polytechnic institution level and was conducted from 1st December 2021 to 31st May 2022 at Sylhet Polytechnic Institute among first year students of different subjects. For this purpose, 906 first year students were enrolled using the purposive sampling technique. A semi-structured questionnaire was used to collect data through a face-to-face interview, as well as height, weight and body mass index (BMI) were measured by standard procedure according to the World Health Organization (WHO). The results showed that most (90.8%) of the respondents were male. The mean heights of male and female respondents were 1.68±0.77 metres and 1.54±0.09 metres, respectively. The mean weight of males was 56.58±9.77 kg and females was 46.48±7.40 kg. The mean BMI index for males was 20.17±3.35 and for females was 19.73±3.51. Normal weight was found in 60.2% of the respondents, underweight was found in 31.7%, overweight 6.6%, and obesity was 1.5% (Obesity class I and II group) among total respondents. The underweight category of the BMI index was significantly associated (p=0.02) with gender. Female respondents have 1.75 times higher odds of being underweight than male respondents. So, the alarming double burden of malnutrition among adolescents and significant female under nutrition revealed here needs a sound national policy on adolescent nutrition. Jalalabad Med J 2024; 21 (1): 17-22